Strategies Used by Teachers in Instilling Religious Values in Elementary School Students - Jepri Wulandari; Rais Aqmaril Abdurrasyid (Elementary Education Journal, 2021)
Background: This study aims to reveal the strategies used by teachers in instilling religious values ​​in SD Karanganyar district and reveal what are the obstacles experienced by teachers in instilling religious values ​​in SD Karanganyar district. The research subjects in this study are; principals, religious teachers, students, and guardians of students. Method: Data collection techniques used are observation, interviews, and documentation. Data validation using source triangulation. The data analysis technique uses source triangulation. Data analysis techniques use data reduction, presentation of data, and concluding. Results: The study results indicate that the strategies used by teachers in instilling religious values ​​include: (1) Familiarizing students with religious activities every day. (2) Provide good examples/examples for students. (3) Accompanying students in carrying out religious values. (4) Controlling student activities, controlling student worship activities by checking control books or mutabaah books owned by students. (5) Give awards to students who want to carry out a program of activities to inculcate religious values. (6) sanctions for students who violate or do not want to carry out the program for inculcating religious values. At the same time, the obstacles experienced by teachers in instilling religious values ​​in students are (1) Lack of facilities and infrastructure to support the implementation of the program for inculcating religious values. (2) diverse student characteristics. (3) Substitute teachers who have not mastered the reading. (4) parents who do not supervise their children's activities at home.